Cancer Among Women Treated in the Veterans Affairs Healthcare System - Zullig, Leah L. (J Womens Health (Larchmt), 2019)
Background: The Veterans Affairs (VA) healthcare system is a high-volume provider of cancer care. Women are the fastest growing patient population using VA healthcare services. Quantifying the types of cancers diagnosed among women in the VA is a critical step toward identifying needed healthcare resources for women Veterans with cancer. Materials and Methods: We obtained data from the VA Central Cancer Registry for cancers newly diagnosed in calendar year 2010. Our analysis was limited to women diagnosed with invasive cancers (e.g., stages I-IV) between January 1, 2010, and December 31, 2010, in the VA healthcare system. We evaluated frequency distributions of incident cancer diagnoses by primary anatomical site, race, and geographic region. For commonly occurring cancers, we reported distribution by stage. Results: We identified 1,330 women diagnosed with invasive cancer in the VA healthcare system in 2010. The most commonly diagnosed cancer among women Veterans was breast (30%), followed by cancers of the respiratory (16%), gastrointestinal (12%), and gynecological systems (12%). The most commonly diagnosed cancers were similar for white and minority women, except white women were significantly more likely to be diagnosed with respiratory cancers (p < 0.01) and minority women were significantly more likely to be diagnosed with gastrointestinal cancers (p = 0.03). Conclusions: Understanding cancer incidence among women Veterans is important for healthcare resource planning. While cancer incidence among women using the VA healthcare system is similar to U.S civilian women, the geographic dispersion and small incidence relative to male cancers raise challenges for high quality, well-coordinated cancer care within the VA.